Structural Properties of CHAPS Micelles, Studied by Molecular Dynamics Simulations - Herrera, Fernando Enrique (2014)
Detergents are essential tools to study biological membranes, and they are frequently used to solubilize lipids and integral membrane proteins. Particularly the nondenaturing zwitterionic detergent usually named CHAPS was designed for membrane biochemistry and integrates the characteristics of the sulfobetaine-type detergents and bile salts. Despite the available experimental data little is known about the molecular structure of its micelles. In this work, molecular dynamics simulations were performed to study the aggregation in micelles of several numbers of CHAPS (≤18) starting from a homogeneous water dilution. The force field parameters to describe the interactions of the molecule were developed and validated. After 50 ns of simulation almost all the systems result in the formation of stable micelles. The molecular shape (gyration radii, volume, surface) and the molecular structure (RDF, salt bridges, H-bonds, SAS) of the micelles were characterized. It was found that the main interactions that lead to the stability of the micelles are the electrostatic ones among the polar groups of the tails and the OH?s from the ring moiety. Unlike micelles of other  compounds, CHAPS show a grainlike heterogeneity with hydrophobic micropockets. The results are in complete agreement with the available experimental information from NMR, TEM, and SAXS studies, allowing the modeling of the molecular structure of CHAPS micelles. Finally, we hope that the new force field parameters for this detergent will be a significant contribution to the knowledge of such an interesting molecule.